The importance of workplace disclosure: perspectives of management and employees - Yusri, Yusniyati; Amran, Azlan (Penerbit Akademia Baru, 2015)
This paper explores management and employees perspective on the importance to disclose workplace and human resource information in annual report. Workplace disclosure is one of the four components of Corporate Social Reporting (CSR). Thirteen managers from 5 GLC and 5 non GLCs and 22 employees were interviewed to gain their awareness and perceptions on the importance to disclose workplace and human resource disclosure in annual report. The findings from the interview analysis showed that there were less significant differences between the management and employees concerning their understanding with respect to CSR and workplace disclosure. The findings revealed that although the interviewees were aware about the CSR concept, their understanding was limited to the company’s responsibility towards the community and the environment. Little significant difference in the opinion was also discovered concerning certain issues comprising the importance of workplace information and the reason for disclosure. The interviewees from employees group perceived that disclosure of workplace information is important and gives advantages to the company but too much disclosure can create a competitive threat to the company.